2016
DOI: 10.1007/s12020-016-1076-5
|View full text |Cite
|
Sign up to set email alerts
|

The visceral adiposity index is associated with insulin sensitivity and IGF-I levels in adults with growth hormone deficiency

Abstract: The visceral adiposity index, based on anthropometric and metabolic parameters, has been shown to be related to adipose tissue function and insulin sensitivity. We aimed to evaluate the performance of the visceral adiposity index in adult patients with growth hormone deficiency. We enrolled 52 patients(mean age 51 ± 13 years) with newly diagnosed growth hormone deficiency and 50 matched healthy subjects as controls at baseline. At baseline and after 12 and 24 months of treatment we evaluated anthropometric mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
1
6
2
1
Order By: Relevance
“…These data contrast with those of Radetti et al, who through evaluation of QUICKI demonstrated a slight degree of insulin resistance in GHD children at baseline compared with controls ( 57 ), while other studies did not show any impairment in Homa-IR ( 12 , 27 , 30 , 58 61 ) or in ISI ( 38 , 62 65 ) in naïve children. No significant difference in fasting glucose, insulin, and HbA1c levels between GHD children and controls were found in many other studies ( 38 , 61 70 ).…”
Section: Resultscontrasting
confidence: 99%
“…These data contrast with those of Radetti et al, who through evaluation of QUICKI demonstrated a slight degree of insulin resistance in GHD children at baseline compared with controls ( 57 ), while other studies did not show any impairment in Homa-IR ( 12 , 27 , 30 , 58 61 ) or in ISI ( 38 , 62 65 ) in naïve children. No significant difference in fasting glucose, insulin, and HbA1c levels between GHD children and controls were found in many other studies ( 38 , 61 70 ).…”
Section: Resultscontrasting
confidence: 99%
“…Clinical evidence suggests that lower GH levels are associated with a deterioration of body composition, which may explain some of the changes observed in AGHD patients. These results highlight the fact that AGHD should be considered as more than a condition lacking GH; it also involves several metabolic disturbances as previously suggested (22).…”
Section: Discussionsupporting
confidence: 81%
“…It is well known that adult patients with GHD show a tendency towards metabolic disorders (higher body mass, unfavourable lipids, and increased leptin and insulin concentrations) and that they return to normal levels following GH treatment [28, 29]. However, the metabolic profile of untreated children with GHD varies in individual reports [48].…”
Section: Discussionmentioning
confidence: 99%
“…It seemed to us that those individuals with GHD who have the lowest bioavailability of IGF-I should present the most severe GHD symptoms. In adults with GHD, strong negative correlations between GH peak concentration and visceral adiposity index (VAI), as well as between IGF-I level and VAI have been proved [29]. VAI takes into account such parameters as BMI and waist circumference, as well as both triglyceride and HDL-cholesterol concentrations.…”
Section: Discussionmentioning
confidence: 99%